NAT10 and N4-acetylcytidine restrain R-loop levels and related inflammatory responses - Debnath, Turja K; Abell, Nathan S; Li, Yi-Ru; Devanathan, Sravan K; Navedo, Enrique; Xhemalçe, Blerta (Science advances, 2025)
N4-acetylcytidine (ac4C) is deposited on diverse RNAs by N-acetyltransferase 10 (NAT10), a protein with high biological relevance for aging and cancer. We performed a comprehensive survey of ac4C using metabolic labeling, sodium cyanoborohydride chemical treatment coupled to next-generation sequencing (NGS), and ac4C antibody-based cell and molecular biology techniques. Our analysis shows that NAT10-dependent ac4C-acetylation is robust in rRNA and specific tRNAs but low/spurious in mRNA. It also revealed an inflammatory signature and mutagenesis at transcriptionally active sites in NAT10-KO cells. This finding led us to explore the role of NAT10 in R-loops, which were recently linked to APOBEC3B-mediated mutagenesis. Our analysis showed that R-loops are ac4C-acetylated in a NAT10-dependent manner. Furthermore, NAT10 restrains the levels of R-loops at a subset of differentially expressed genes in a catalytic activity-dependent manner. Together with cellular biology data showing ac4C-modified RNA in endosomal structures, we propose that increased levels of ac4C-unmodified RNAs, likely derived from R-loops, in endosomal structures induce inflammatory responses.N4-acetylcytidine (ac4C) is deposited on diverse RNAs by N-acetyltransferase 10 (NAT10), a protein with high biological relevance for aging and cancer. We performed a comprehensive survey of ac4C using metabolic labeling, sodium cyanoborohydride chemical treatment coupled to next-generation sequencing (NGS), and ac4C antibody-based cell and molecular biology techniques. Our analysis shows that NAT10-dependent ac4C-acetylation is robust in rRNA and specific tRNAs but low/spurious in mRNA. It also revealed an inflammatory signature and mutagenesis at transcriptionally active sites in NAT10-KO cells. This finding led us to explore the role of NAT10 in R-loops, which were recently linked to APOBEC3B-mediated mutagenesis. Our analysis showed that R-loops are ac4C-acetylated in a NAT10-dependent manner. Furthermore, NAT10 restrains the levels of R-loops at a subset of differentially expressed genes in a catalytic activity-dependent manner. Together with cellular biology data showing ac4C-modified RNA in endosomal structures, we propose that increased levels of ac4C-unmodified RNAs, likely derived from R-loops, in endosomal structures induce inflammatory responses.